2011
DOI: 10.1515/rns.2011.041
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor necrosis factor receptor superfamily members in mammalian brain development, function and homeostasis

Abstract: Tumor necrosis factor receptor superfamily (TNFRSF) members were initially identified as immunological mediators, and are still commonly perceived as immunological molecules. However, our understanding of the diversity of TNFRSF members' roles in mammalian physiology has grown significantly since the first discovery of TNFRp55 (TNFRSF1) in 1975. In particular, the last decade has provided evidence for important roles in brain development, function and the emergent field of neuronal homeostasis. Recent evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 273 publications
(450 reference statements)
1
22
0
1
Order By: Relevance
“…TL1A and DR3 generally are known for low basal expression with most research focused on lymphocytes and autoimmune diseases [42], although previous studies have identified TL1A mRNA in mouse brain [28]. A characteristic of TNF receptor signaling is amplification of ligands, receptors, and cascade signaling components within and across cells; in brain this likely involves glia and neurons [3,24]. We found TRADD, FADD, and pFADD expression increased about fourfold, consistent with amplification of TL1A, DR3, and FasL initiating TL1A-DR3-TRADD-FADD-procaspase 8 complexes referred to as DISC ((DISC,27)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TL1A and DR3 generally are known for low basal expression with most research focused on lymphocytes and autoimmune diseases [42], although previous studies have identified TL1A mRNA in mouse brain [28]. A characteristic of TNF receptor signaling is amplification of ligands, receptors, and cascade signaling components within and across cells; in brain this likely involves glia and neurons [3,24]. We found TRADD, FADD, and pFADD expression increased about fourfold, consistent with amplification of TL1A, DR3, and FasL initiating TL1A-DR3-TRADD-FADD-procaspase 8 complexes referred to as DISC ((DISC,27)).…”
Section: Discussionmentioning
confidence: 99%
“…DRs initiate a death-inducing signaling complex (DISC) of proteins that share DDs leading to CC3-induced cell death through multiple paths. The DD-containing receptors death receptor 3 (DR3, TNFRSF25) and Fas receptor (Fas, FasR, CD95, TNFRSF6) are expressed at low levels in the hippocampus of rodents and humans [24]. The TNFSF agonists TNF-like 1A (TL1A, TNFSF15, VEGI) for DR3 and Fas ligand (FasL, TNFSF6, CD95L) for FasR, are also expressed in brain, as are components of the DISC, i.e., the DDsignaling protein Fas-associated death domain (FADD) and caspase-8, an initiator caspase.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that multiple mechanisms regulate the effects of cytokines on offspring brain development, with specific mechanisms depending on timing of exposure. These include: dysregulation of nerve growth factors (Schobitz et al 1993; Anisman & Merali, 2002; Gilmore et al 2003; Twohig et al 2011); loss of dendritic connections (Marx et al 2001; Gilmore et al 2004; Twohig et al 2011) and white matter connectivity (Yoon et al 1996; Dammann & Leviton, 1997); apoptosis (Hu et al 1997); dysregulation of neurotransmitters (Zalcman et al 1994; Behrens et al 2008); and hormonal dysregulation (Schobitz et al 1993; Anisman & Merali, 2002) impeding healthy sexual differentiation of the brain (Handa et al 1994; Kawata, 1995; Tobet & Hanna, 1997; Goldstein et al 2001; Tobet, 2002) and brain aging (Zietz et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to the developing brain, it has recently been demonstrated that microglia play a crucial role in normal postnatal synaptic pruning via complement signaling (Schafer et al, 2012). Further, members of the tumor necrosis factor receptor super family have been implicated in the regulation of neuronal progenitor proliferation, differentiation and patterning (Saliba and Henrot, 2001; Twohig et al, 2011). These findings highlight the complex interplay between the CNS and immune response, which is likely to influence both normal brain development as well as the brain's response to injury (Bilbo and Schwarz, 2012).…”
Section: Innate and Adaptive Immunitymentioning
confidence: 99%